New calcium germanium nitrides: Ca2GeN2, Ca4GeN4, and Ca5Ge2N6. - Clarke, S; DiSalvo, F (2000)
We report three new calcium germanium nitrides synthesized as crystals from the elements in sealed niobium tubes at 760 degrees C using liquid sodium as a growth medium. Black Ca2GeN2 is isostructural with the previously reported strontium analogue. It is tetragonal P4(2)/mbc (no. 135) with a = 11.2004(8) A, c = 5.0482(6) A, and Z = 8. It contains GeN2(4-) units which have 18 valence electrons, and consequently are bent, like the isoelectronic molecule SO2. In contrast, clear, orange Ca4GeN4 with fully oxidized germanium contains isolated GeN4(8-) tetrahedra and is monoclinic P2(1)/c (no. 14) with a = 9.2823(8) A, b = 6.0429(5) A, c = 11.1612(9) A, beta = 116.498(6) degrees, and Z = 4. Clear, colorless Ca5Ge2N6, also with fully oxidized germanium, contains infinite chains, 1 infinity[GeN2N2/2(5-)], of corner-sharing tetrahedra similar to those found in pyroxenes. However, the precise structure of this latter phase has not yet been determined because of twinning problems.